Plasticity of the Berry Ripening Program in a White Grape Variety - Dal Santo, Silvia; Fasoli, Marianna; Negri, Stefano; D'Incà, Erica; Vicenzi, Nazareno; Guzzo, Flavia; Tornielli, Giovanni Battista; Pezzotti, Mario; Zenoni, Sara (Frontiers in Plant Science, 2016)
Grapevine (Vitis vinifera L) is considered one of the most environmentally sensitive crops and is characterized by broad phenotypic plasticity, offering important advantages such as the large range of different wines that can be produced from the same cultivar, and the adaptation of existing cultivars to diverse growing regions. The uniqueness of berry quality traits reflects complex interactions between the grapevine plant and the combination of natural factors and human cultural practices, defined as terroir, which leads to the expression of wine typicity. Despite the scientific and commercial importance of genotype interactions with growing conditions, few studies have characterized the genes and metabolites directly involved in this phenomenon. Here we used two large-scale analytical approaches to explore the metabolomic and transcriptomic basis of the broad phenotypic plasticity of Garganega, a white berry variety grown at four sites characterized by different pedoclimatic conditions (altitudes, soil texture and composition). These conditions determine berry ripening dynamics in terms of sugar accumulation and the abundance of phenolic compounds. Multivariate analysis unraveled a highly plastic metabolomic response to different environments, especially the accumulation of hydroxycinnamic and hydroxybenzoic acids and flavonols. Principal component analysis revealed that the four sites strongly affected the berry transcriptome allowing the identification of environmentally-modulated genes and the plasticity of commonly-modulated transcripts at different sites. Many genes that control transcription, translation, transport and carbohydrate metabolism showed different expression depending on the environmental conditions, indicating a key role in the observed transcriptomic plasticity of Garganega berries. Interestingly, genes representing the phenylpropanoid/flavonoid pathway showed plastic responses to the environment mirroring the accumulation of the corresponding metabolites. The comparison of Garganega and Corvina berries showed that the metabolism of phenolic compounds is more plastic in ripening Garganega berries under different pedoclimatic conditions.